Polyvinylcarbazole films: Applications for chemical sensors - Kruglenko, I.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The adsorption properties of polyvinylcarbazole (PVC) films as sensitive layers of quartz crystal microbalance (QCM) sensors have been studied. Different organic vapors and complex mixture (a cologne) were tested as analytes. PVC films have demonstrated different adsorption properties under different temperatures. This makes it a perspective material for sensor applications.